Child Custody in Divorce of Husband Abandonment: Judge's Subjectivity Based on the Benefit of the Child Determination No. 310/Pdt.G/2023/MS. Bna - Rahma Fitria Marta; Fakhrurrazi M. Yunus; Nurul Fithria; Ozioma Victoria Uchime; Nur Farahin Afiqah Daud (al-Battar: Jurnal Pamungkas Hukum, 2026)
Divorce due to husband neglect is a family problem that has a significant impact on the protection of children's rights, especially in the determination of custody (hadhanah). This condition requires legal considerations that put the best interests of children as the top priority. This research focuses on the Decision of the Banda Aceh Syar'iyah Court Number 310/Pdt.G/2023/MS. Bna to examine the extent of the judge's consideration in determining child custody in the case of husband neglect. The purpose of this study is to analyze the basis of the judges' deliberations and assess them from the perspective of Islamic law. This study uses a qualitative method with a normative juridical approach. Data was obtained through a literature study that included analysis of court decisions, laws and regulations, and relevant fiqh literature. The data was analyzed descriptive-analytically to identify the suitability between judges' considerations, positive legal norms, and Islamic legal principles in determining child custody. The results of the study showed that the panel of judges determined the right of hadhanah to the mother with the consideration that the husband was proven to have committed neglect, did not provide maintenance, and did not meet the moral feasibility in raising children. This consideration is in line with the provisions of Article 105 of the Compilation of Islamic Law and the principle of the welfare of children in Islamic law. Thus, the ruling reflects the harmonization between positive law and Islamic law in ensuring the best protection for children after divorce. Therefore, this study recommends that courts consistently prioritize the principle of the best interests of the child and strengthen benefit-based considerations in every custody decision in family neglect cases.